Supportive Care for Severe Tetanus in the Intensive Care Unit: A Narrative Review (Jurnal Anestesiologi dan Terapi Intensif, 2026)
Tetanus is an acute infectious disease caused by Clostridium tetani and remains associated with high mortality, particularly in severe cases requiring intensive care unit (ICU) admission. The neurotoxin tetanospasmin induces persistent muscle spasms, autonomic dysfunction, and respiratory failure, rendering ICU management complex and resource-intensive. This narrative review aims to synthesize current evidence on multimodal supportive care strategies that improve clinical outcomes in patients with severe tetanus managed in the ICU. This literature review identifies several interrelated components as central to successful management, including early airway control and mechanical ventilation, optimized sedation and spasm control using benzodiazepines, magnesium sulfate, and selected adjuvant agents, targeted nutritional and metabolic support through early enteral feeding, prevention of ICU-related complications, and early rehabilitation to mitigate ICU-acquired weakness. Collectively, evidence indicates that a comprehensive, evidence-based supportive care approach improves hemodynamic stability, reduces complication rates, and facilitates functional recovery in patients with severe tetanus.
Keywords: Tetanus; Intensive Care Units; Supportive Care; Mechanical Ventilation; Sedation